Design of Ergonomic Tables and Chair for Special Needs Students (Case Study: Elia Junior High School Surabaya) - Aryanny, Enny; Santoso, Budi; Alrianto, Wahyu Putra (Future Science)
Elia Junior High School is one of the private middle schools in Surabaya. The school has special needs students. Elia Junior High School uses normal sized school chairs and tables for students in general, when using it they often complaints of pain in the neck, and shoulders to the size of the table is too high and the table is not flexible, pain in the spine caused the back of the chair too upright, also the table does not have a drawer and a place to put a drink and hang shoes. The purpose of this study to design school tables and chairs for special needs students with ergonomic at Elia Junior High School Surabaya with the Anthropometry approach to reduce the grievances felt by these junior high school students. Finally, on the results of the study, the size of ergonomic school tables and chair of the seat high is 40.31 cm, the seat length is 45 cm, the seat width is 35 cm, the high back of the chair is 50 cm, the seatback width is 45.44 cm, the high t of the bottom table is 54 cm, the high of the top table is 70 cm, the length, and width of the table is 54.24 cm and the high of the drawer is 10 cm. These school tables and chairs are flexible because height and inclination can be adjusted to the dimensions of the student's body and have a drawer for storing drinks, and a place to hang shoes.